X-Linked Retinoschisis in Juveniles: Follow-Up by Optical Coherence Tomography. (14th February 2017) - Hu, Qin-rui; Huang, Lv-zhen; Chen, Xiao-li; Xia, Hui-ka; Li, Tian-qi; Li, Xiao-xin
Abstract : Purpose. To explore the structural progression of X-linked retinoschisis (XLRS) in patients by using spectral-domain optical coherence tomography (SD-OCT). Design. Retrospective, observational study. Methods. Patients who were diagnosed with XLRS by genetic testing underwent comprehensive ophthalmological examinations from December 2014 to October 2016. Each eye was measured by SD-OCT using the same clinical protocol. A correlation between best-corrected visual acuity (VA) and SD-OCT measurements was observed. Results. Six patients demonstrated retinoschisis (12 eyes) and typical foveal cyst-like cavities (10 eyes) on SD-OCT images with a mean logMAR VA of 0.48. The median age was 7.5 years at the initial visit. Their foveal retinal thickness (516.9  μ m) and choroid thickness (351.4  μ m) decreased at a rate of 38.1 and 7.5  μ m, respectively, at the 10.5-month follow-up visit; however, there were no significant differences (P = 0.622 and P = 0.406, resp.). There was no significant correlation between VA, the foveal retinal thickness, and subfoveal choroid thickness. Conclusions. SD-OCT images for XLRS patients during the juvenile period revealed no significant changes in the fundus structure, including the foveal retinal thickness and choroid thickness within one-year follow-up. There was a lack of correlation between VA, foveal retinal thickness, and subfoveal choroid thickness.